Optimization of decision making to avoid stochastically predicted air traffic conflicts - Васильєв, В.М. (Proceedings of National Aviation University (archive), 2005)
The method of decision-making optimization on planning an aircraft trajectory to avoid potential conflict with restricted minimal level of separation standard is proposed. Evaluation and monitoring the conflict probability are made using the probabilistic composite method.